Managing Inclusive Education in a Primary School at UNG Laboratory Elementary School - Rahmatiya Husain; Hermanto Hermanto (Journal of Educational Sciences, 2026)
Inclusive education in primary schools continues to face managerial and resource-related challenges, including in Gorontalo City. This study aims to analyze the management of inclusive education at the UNG Laboratory Elementary School. The study employed a descriptive qualitative approach at the UNG Laboratory Elementary School. Data were collected through in-depth interviews, non-participatory observation, and documentation studies involving the principal, the inclusion team, class teachers, shadow teachers, the school treasurer, and parents of students with special needs. Data analysis was conducted inductively using the interactive analysis model of Miles, Huberman, and Saldana. The results indicate that inclusive education at the UNG Laboratory Elementary School has been integrated into the school management system. Planning is based on identifying student needs from the admission stage; organization is supported by forming an inclusion team and collaboratively allocating roles; implementation is carried out through adaptive learning in regular classes and partial mentoring; and supervision is conducted reflectively through parents. This research confirms that the success of managing an inclusive school is determined more by adaptive leadership, a collaborative culture, and the alignment with real school conditions to support sustainable inclusive education implementation in primary schools.